On-Chip Grating Based Multi-wavelength Optical Reflector for Multichannel Optoelectronic Devices - Kaur, Jaspreet (My University, 2014)
Optical Grating is a long topic with a long history. It has been extensively studied over the years due to its wide application in holography, spectroscopy, lasers and many other optoelectronic devices.One of theinnovative forms of grating is the High-index contrast grating (HCG). It is possible to get multiwavelength reflections by optimizing the HCG parameters. The recent advances of high-index-contrast (HCG) grating and its applications in optoelectronic devices are reviewed. The power Reflectivity at different wavelength under the variation of different grating parameters is demonstrated on the simulation. Grating periods, grating spacing and grating removal are the parameters varied for the Reflectivity analysis and also effects of the parameters on Reflectivity are studied. Standard Sampled grating array is designed and 2D simulation is performed with finite difference method. Reflectivity of Sampled Grating array is observed as 100% at multiple wavelengths. Such type of Grating array can also find application in the field of optoelectronic devices. Further, modified form of sampled grating structure can perform filtering operation. Thus, this approach of Modified Sampled grating design can work as a filter.
ME, ECED
Keywords: Multiwavelength Reflector; Integrated Optoelectronics